Feasibility of reirradiation and treatment outcome in a previously irradiated territory in head-and-neck malignancies - Sweety Gupta; Amit Gupta; Prekshi Choudhary; Ashish Gupta; Manjari Shah; Shashank Srinivasan; Ruchir Tandon; Sudarsan De (The Egyptian Journal of Otolaryngology, 2018)
Abstract Introduction Despite combined modality treatment, local persistent or recurrent disease is a primary cause of treatment failure in 30–50% of patients with advanced head-and-neck cancer (HNC). The role of reirradiation is feared because of increased risk of toxicity due to the previously irradiated target volume. In the present study, we have evaluated reirradiation by image-guided intensity-modulated radiotherapy in recurrent and second primary HNCs and its outcome. Materials and methods In all, 24 patients with recurrence or second primary tumors in HNC were included in the study conducted between January 2009 to August 2014. All patients were treated by the image-guided intensity-modulated radiotherapy technique. The most common site of recurrence/second primary was oral tongue. The time interval between initial radiotherapy and reirradiation ranged from 8 months to 17 years. Statistical analysis used The association between qualitative variables was tested using the χ2-test. Statistical significance was interpreted using an arbitrary cut-off of P=0.05. Kaplan–Meier Survival graph was plotted to depict the survival pattern of the study patients. Results The planning target volume volume of reirradiation ranged from 26.72 to 469.32 ml (median: 118.71 ml). Toxicity was more in patients receiving concurrent chemoradiation and in patients with less interval time between reirradiation. Out of the 24 patients, nine were no evidence of disease, eight patients expired (five disease progression, two comorbidities, and one due to hematemesis after the development of third primary), two recurred, one developed distant metastases, and four were lost to follow-up. Conclusion Surgical resection, with or without reirradiaton, provides the highest likelihood for successful salvage in locoregional (LR) recurrences in HNCs. Patients reirradiated after a long time from initial irradiation have better tolerance.